Common variants in SOCS7 gene predict obesity, disturbances in lipid metabolism and insulin resistance - Tellechea, Mariana Lorena (2012)
Background and Aims: Specific Suppressor Of Cytokine Signaling (SOCS) members, such as SOCS7, may play a role in the development of insulin resistance (IR) owing to their ability to inhibit insulin signaling pathways. The objective was to explore the association between common variants and related haplotypes in SOCS7 gene and metabolic traits related to obesity, lipid metabolism and IR. Methods and Results: 780 unrelated men were included in a cross-sectional study. We selected three tagged SNPs that capture 100% of SNPs with minor allele frequency ≥ 0.10. Analyses were done separately for each SNP and followed up by haplotype analysis. rs8074124C was associated with both obesity (P = 0.005) and abdominal obesity (P = 0.002) and allele C carriers showed, in comparison with TT-carriers, lower BMI (P = 0.001) and waist circumference (P = 0.001). rs8074124CC- carriers showed lower fasting insulin (P = 0.017) and HOMA-IR (P = 0.018) than allele T carriers. rs12051836C was associated with hypertriglyceridemia (P = 0.009) and hypertriglyceridemic waist (P = 0.006). rs12051836CC- carriers showed lower fasting insulin (P = 0.043) and HOMA-IR (P = 0.042). Haplotype-based association analysis (rs8074124 and rs12051836 in that order) showed associations with lipid and obesity -related phenotypes, consistent with single locus analysis. Haplotype analysis also revealed association between haplotype CT and both decreased HDL-C (P = 0.026) and HDL-C (P = 0.014) as a continuous variable. Conclusion: We found, for the first time, significant associations between SOCS7 common variants and related haplotypes and obesity, IR and lipid metabolism disorders.